23.5%-efficient silicon heterojunction silicon solar cell using molybdenum oxide as hole-selective contact. (April 2020) - Dréon, Julie; Jeangros, Quentin; Cattin, Jean; Haschke, Jan; Antognini, Luca; Ballif, Christophe; Boccard, Mathieu
Abstract: Interest in silicon heterojunction solar cells is growing due to their manufacturing simplicity and record efficiencies. However, a significant limitation of these devices still stems from parasitic light absorption in the amorphous silicon layers. This can be mitigated by replacing the traditional (p) and (n) doped amorphous silicon selective layers by other materials. While promising results have been achieved using molybdenum oxide (MoOx ) as a front-side hole-selective layer, charge transport mechanisms in that contact stack have remained elusive and device efficiencies below predictions. We carefully analyze the influence of the MoOx and intrinsic a-Si:H thicknesses on current-voltage properties and discuss transport and performance-loss mechanisms. In particular, we find that thinning down the MoOx and (i)a-Si:H layers (down to 4 nm and 6 nm respectively) mitigates parasitic sub-bandgap MoOx optical absorption and drastically enhances charge transport, while still providing excellent passivation and selectivity. High-resolution transmission microscopy reveals that such thin MoOx layer remains continuous and, while slightly sub-stoechiometric, exhibits a chemistry close to MoO3 . A screen-printed device reaching a certified efficiency of 23.5% and a fill factor of 81.8% is demonstrated, bridging the gap with traditional Si-based contacts and demonstrating that dopant-free selective contacts can rival traditional approaches. Graphical abstract: Image 1 Highlights: Silicon heterojunction solar cell with ultra-thin MoOx-based contact was processed. To better understand this contact, thickness of both MoOx and (i)a-Si:H was varied. Current-voltage and optical properties were analyzed to discuss loss mechanisms. Microstructural STEM and EELS analysis was carried out to check MoOx film properties. A 23.5%-efficient device with 81.8% FF was achieved.